Faktor-Faktor yang Mempengaruhi Sektor Pariwisata dalam Meningkatkan PDRB di Kota Langsa - Muhammad Furqan; Sefi Ratiwi; Fatima Baen; Puti Andiny (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to analyze the factors influencing the tourism sector in increasing Gross Regional Domestic Product (PDRB) in Langsa City. It uses secondary data in the form of time series for the period 2013-2022, published by the Central Statistics Agency (BPS) of Langsa City. The data analysis method applies multiple regression analysis using SPSS software. The results show that Wholesale & Retail Trade has a positive but insignificant effect on PDRB in Langsa City. Transportation & Warehousing also has a positive but insignificant effect on PDRB in Langsa City. Additionally, Accommodation & Food Services have a positive but insignificant effect on PDRB. Simultaneously, Wholesale & Retail Trade, Transportation & Warehousing, and Accommodation & Food Services have a significant effect on PDRB in Langsa City.